A Novel Mutation p.A59P in N-Terminal Domain of Methyl-CpG–Binding Protein 2 Confers Phenotypic Variability in 3 Cases of Tunisian Rett Patients: Clinical Evaluations and In Silico Investigations. (November 2015) - Kharrat, Marwa; Hsairi, Ines; Fendri-Kriaa, Nourhene; Kenoun, Houda; Othmen, Houda Ben; Ben Mahmoud, Afif; Ghorbel, Rania; Abid, Imen; Triki, Chahnez; Fakhfakh, Faiza
Rett syndrome is a monogenic X-linked dominant neurodevelopmental disorder related to mutation in MECP2, which encodes the methyl-CpG–binding protein MeCP2. The aim of this study was to search for mutations of MECP2 gene in Tunisian Rett patients and to evaluate the impact of the found variants on structural and functional features of MeCP2. The result of mutation analysis revealed that 3 Rett patients shared the same novel heterozygous point mutation c.175G>C (p.A59P). The p.A59P mutation was located in a conserved amino acid in the N-terminal segment of MeCP2. This novel mutation confers a phenotypic variability with different clinical severity scores (3, 8, and 9) and predicted by Sift and PolyPhen to be damaging. Modeling results showed that p.A59P adds 2 hydrogen bonds and changes the structural conformation of MeCP2 with a significant root mean square deviation value (9.66 Å), suggesting that this mutation could probably affect the conformation, function and stability of MeCP2.